Population Genetic Structure and Connectivity of the European Lobster Homarus gammarus in the Adriatic and Mediterranean Seas - Pavičić, Mišo; Žužul, Iva; Matić-Skoko, Sanja; Triantafyllidis, Alexandros; Grati, Fabio; Durieux, Eric D. H.; Celić, Igor; Šegvić-Bubić, Tanja (Frontiers in Genetics, 2020)
Highly selective fishing has the potential to permanently change the characteristics within a population and could drive the decline of genetic diversity. European lobster is an intensively fished crustacean species in the Adriatic Sea which reaches high market value. Since knowledge of population structure and dynamics is important for effective fisheries management, in this study, we used 14 neutral microsatellites loci and partial mitochondrial COI region sequencing to explore population connectivity and genetic structure by comparing samples from the Adriatic Sea and the adjacent basins of the Mediterranean Sea. The obtained results suggest that neutral genetic diversity has not been significantly affected by reductions in population size due to overfishing, habitat loss and other anthropogenic activities. Global genetic differentiation across all populations was low (FST = 0.0062). Populations from the Adriatic Sea were panmictic, while genetic differentiation was found among populations from different Mediterranean basins. Analysis of gene flow for European lobster suggest that populations in the north eastern Adriatic act as a source for surrounding areas, highlighting the need to protect these populations by establishing interconnected MPAs that will be beneficial for both fisheries and conservation management.